(untitled) (International journal of medical sciences, 2026)
This scientific article presents modern concepts of prions, their origin and structure, the biological basis of prion diseases, and their practical significance. The study analyzes the ability of prion proteins to transform into pathogenic forms without genetic or epigenetic alterations, their association with neurodegenerative diseases, as well as their importance in medicine, veterinary science, and food safety. Special attention is paid to the unique infectious nature of prions, which challenges classical biological paradigms and raises important issues related to biosafety and epidemiology.